2017
DOI: 10.1371/journal.ppat.1006263
|View full text |Cite
|
Sign up to set email alerts
|

Deacetylation of sialic acid by esterases potentiates pneumococcal neuraminidase activity for mucin utilization, colonization and virulence

Abstract: Pneumococcal neuraminidase is a key enzyme for sequential deglycosylation of host glycans, and plays an important role in host survival, colonization, and pathogenesis of infections caused by Streptococcus pneumoniae. One of the factors that can affect the activity of neuraminidase is the amount and position of acetylation present in its substrate sialic acid. We hypothesised that pneumococcal esterases potentiate neuraminidase activity by removing acetylation from sialic acid, and that will have a major effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 74 publications
0
57
1
Order By: Relevance
“…The crystal structure of EstA reveals a dimeric organization that is stabilized by the presence of a calcium ion. Three other esterases have been identified in S. pneumoniae, but only EstA was found to contribute to the growth of the bacterium on BSM [89]. Three other esterases have been identified in S. pneumoniae, but only EstA was found to contribute to the growth of the bacterium on BSM [89].…”
Section: Degradation Of O-linked and Related Glycansmentioning
confidence: 99%
See 2 more Smart Citations
“…The crystal structure of EstA reveals a dimeric organization that is stabilized by the presence of a calcium ion. Three other esterases have been identified in S. pneumoniae, but only EstA was found to contribute to the growth of the bacterium on BSM [89]. Three other esterases have been identified in S. pneumoniae, but only EstA was found to contribute to the growth of the bacterium on BSM [89].…”
Section: Degradation Of O-linked and Related Glycansmentioning
confidence: 99%
“…However, there is also a wealth of evidence to show that the role of Nglycan degradation in the host-pathogen interaction extends beyond nutrition. NanA, as the initiator of complex N-glycan degradation, has been identified as a key virulence factor in S. pneumoniae that contributes to adherence [69,78,[80][81][82], biofilm formation [81][82][83][84], tissue invasion [69,85], colonization [82,[86][87][88][89], persistence [86,87], immune Box 2. NanA, as the initiator of complex N-glycan degradation, has been identified as a key virulence factor in S. pneumoniae that contributes to adherence [69,78,[80][81][82], biofilm formation [81][82][83][84], tissue invasion [69,85], colonization [82,[86][87][88][89], persistence [86,87], immune Box 2.…”
Section: Role Of N-glycan Degradation In Virulencementioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported a substantially reduced bacterial burden in the lungs of mice infected intranasally with nan A and/or nan B gene deletion mutant strains and improved host survival [39,40,68]. NanA was shown to contribute to nasopharyngeal colonisation [41,43,6870].…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial CEs have important physiological functions, which were proven by that the CE mutant shows growth retardation [19,20]. However, only few bacterial CEs have been identified and investigated in detail.…”
Section: Introductionmentioning
confidence: 99%